Environmental Journalism in Online Media teras7.com for Delivering Flood Disaster in South Kalimantan - Astinana Yuliarti; Putri Ayu Hidayatur Rofiqoh; Rosalina Kumalawati (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2025)
Fast and accurate information is a need for people throughout Indonesia, including South Kalimantan, including information related to disaster events. South Kalimantan is an area that has a high level of vulnerability to flood disasters every year. This article was written with the aim of revealing the framing of flood-related news carried out by the online media Teras.7, which consists of related news before the disaster occurred, when the disaster occurred and after the disaster occurred. The limitation of this research is that the news analysis focuses on only one online media, namely terrace7.com. The method used to analyze the data is descriptive qualitative with Robert Etnman's Framing analysis approach. There are nine news stories analyzed which illustrate that the news presented by the online media teras7.com has fulfilled the four elements of Etnman's framing, where each report always begins with define problem to explain flood events in an area, diagnosis causes which explain what happened and who caused it. involved, then the element of making moral judgment in the news article accompanied by strengthening arguments supported by statements from sources and the last element, namely treatment recommendations containing recommendations, solutions and follow-up actions that must be carried out.